The Open Defecation Free Program Evaluation Using the Context, Input, Process, and Product Model in Jambi, Indonesia - Guspianto, Guspianto; Rini, Willia Novita Eka; Wardiah, Rizalia; Desmaryani, Susi; Herlina, Herlina (UI Scholars Hub, 2024)
The Open Defecation Free (ODF) program was initiated by the government to increase access to healthy latrines. This study aimed to evaluate the ODF program using the CIPP evaluation model. A qualitative and exploratory descriptive method was adopted to investigate informants' experiences regarding the program's implementation. Data was explored through semi-structured interviews with 17 informants and analyzed using content analysis. The results showed that the program was crucial as numerous people engaged in open defecation due to economic, geographical, cultural, and knowledge factors. The absence of ODF policy was due to lack of priority, limited government and private support, insufficient human resources, inadequate infrastructure, and budget constraints. The ODF program was considered unimportant and tended to follow stunting programs, reflecting the low commitment. The biggest opportunity was implementing an integrated ODF with a stunting reduction program by allocating a special budget. Thus, primary health care is expected to optimize activities further to trigger the ODF program within the environment.